(untitled) (Revista Internacional de Folkcomunicação, 2025)
This article proposes the concept of folkfeminism as an analytical category to understand women’s communicational practices in popular cultures in Latin America. By articulating folk communication and Latin American feminisms, folkfeminism highlights how women in popular contexts construct narratives, performances, and spaces of symbolic resistance, challenging social and gender hierarchies. The proposal is based on a bibliographic review, integrating decolonial and community epistemologies, and opens pathways for future empirical research on female communicational agency.